Circulatory stem cells of Styela plicata (Lesueur, 1823) (Tunicata: Stelidae): an evolutionary approach - Merino, Juan Jiménez (2018)
Styelid ascidians are diverse in developmental modes, varying from strictly sexual solitary species to highly integrated colonies. Circulatory stem cells (CSCs) accomplish fundamental roles in developmental processes of styelid ascidians. In the colonial styelids, CSCs enable budding and are capable of giving origin to the germline in certain species. The function of these cells have been tested experimentally in models within Styelidae. However, the understanding of coloniality as an evolutionary novelty requires reconstructing the possible ancestral CSCs characteristics in Styelidae. To address this issue, this work analyzes the possible developmental origin and the identity of putative CSCs among blood cell populations. The first chapter of this dissertation aimed to characterize and compare the hemocyte populations in two solitary styelids: Styela plicata and Styela canopus. In addition, the early development, the metamorphosis and the early maturation were compared in both species. After metamorphosis, S. canopus briefly develops a network of extracorporeal vessels with numerous terminal ampullae. These characters are usually associated to colonial ascidians, and were not found in S. plicata. With respect to the hemocyte populations, similar morphotypes were present in both species. However, S. canopus shows a lower frequency of vacuolated cells, which may be due to a reduced level of cytotoxicity in the tunic relative to S. plicata. These differences observed between S. canopus and S. plicata may be related to differences in the degrees of gregariousness or body size among the two species. In order to investigate possible approaches to distinguish and isolate CSC populations in a solitary styelid model, I used imaging flow cytometry. Putative CSCs were identified through measurement of morphological parameters and aldehyde dehydrogenase (ALDH) activity. The correlation between these parameters allowed to determine 2 gates enriched with particular cell types. A significant difference was found on the ALDH+ population within a gate of cells with low granularity, suggesting the presence of cells among circulatory hemocytes. To scrutinize the biogenesis of CSCs in S. plicata, I present a description of a candidate hematopoietic niche in this species. An exhaustive histological survey for hemoblast-like cells was performed, and complemented with immunohistochemistry with stem cell (piwi) and proliferation (pHH3) markers. The morphological and expression profiles of the intestine support the intestinal submucosa (IS) as a hematopoietic niche. At this region there are aggregations of cells with and undifferentiated morphological profile, corroborated by ultrastructural analysis. Furthermore, the IS holds high cellular proliferation and frequency of piwi+ cells. Ascidians are considered interesting models to investigate asexual reproduction and modular development. This study represents an advancement towards understanding the processes, cell populations and structures that may be related to facilitating the appearance of this evolutionary novelty